Parallel approaches to the segmentation of free-hand drawings - Canham, R.C.; Smith, S.L.; Tyrrell, A.M. (Proceedings of EUROMICRO 96. 22nd Euromicro Conference. Beyond 2000: Hardware and Software Design Strategies, 1996)
This paper describes the initial steps in the development of a parallel approach to the segmentation of free-hand drawings as part of a subject's neuropsychological assessment. The drawings to be segmented are responses to the widely used Rey-Osterrieth Complex Figure Test which comprises a number of simple geometric shapes such as rectangles and triangles with connecting lines. The need for a parallel approach in the segmentation of the drawings is discussed and a hierarchical solution proposed which reduces substantially the processing time required to perform the operation. Results are presented for a first approach to the segmentation and identification of substructures within the drawing based on a modified simple template matching algorithm. The results are promising but underline the complexity of segmenting such freehand line drawings.